THE TERRITORIAL QUESTION OF THE ROMA CAPITALE REGION - Francesco Maria Olivieri; Marco Brogna (Bollettino della Società Geografica Italiana, 2019)
The specific role of the State Capital city has been increasing interesting and now it results widely argue, because of the Rome’ Capital institution. This theme is trans-disciplinary and geographical studies are such important to the Italian territorial organization: it has originated by the debate about the Italian space at the end of XIX century and it has been linked to the centralism-federalism dichotomy. Anyway, the space organization applies to different driven concepts (i.e. functionalism, law, administrative). The aim of the paper is refers to a specific necessity of a careful consideration based on a territorial contribution to the local community needs. The methodology refers to European system law to local authorities of multilevel governance and the succeeding Titolo V Constitution reform (2001-2014). Indeed the law status of Rome Capital City has been now developing (l.42/2009). Thecase of Rome is such important to the allocation of authorities and powers at different scales. The acknowledgment of this role of Capital is a necessary condition but it is no sufficient too, in spite of the recognition of the government best level and the group of authorities. The last question of this topic is about a new proposal to individuate the best institution on two different characters: law for the authorities and territorial for the dimension.